Ocean engineering anticorrosive paint and preparation method thereof
By using components such as fluorocarbon resin in marine engineering anticorrosion coatings, a complex physical barrier structure and chemical corrosion inhibition layer is formed, which solves the problem of insufficient anti-corrosion of existing coatings and achieves more efficient anti-corrosion and longer service life.
Patent Information
- Application Number
- CN202411606320.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing marine engineering anticorrosion coatings are still poor in the face of long-term use, strong electrolytes, temperature, pressure and marine organisms.
The combination of fluorocarbon resin, modified synthetic mica, modified basalt fiber, modified carbon nanotubes, nanosilica, nanozinc oxide, nanotitanium dioxide, carbon fiber, zinc phosphate, plant extracts and other components is used to form complex The physical barrier structure and chemical corrosion inhibitor layer improve the corrosion resistance of the paint.
It significantly improves the anti-corrosion, mechanical properties, anti-aging properties and environmental protection properties of the coating, can effectively resist long-term corrosion in the marine environment, and extend the service life of marine engineering facilities.
Smart Images

Figure BDA0005129671090000161 
Figure BDA0005129671090000171
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to an anti-corrosion coating for marine engineering and a preparation method thereof. Background Art
[0002] With the continuous development and utilization of marine resources by human beings, marine engineering construction has developed rapidly. From offshore oil drilling platforms to cross-sea bridges, from submarine tunnels to port terminals, various marine engineering facilities have sprung up like mushrooms after rain. However, the marine environment is extremely harsh, posing a serious corrosion threat to these engineering facilities, so marine engineering anti-corrosion coatings came into being.
[0003] The ocean is a complex and harsh corrosive environment. First of all, seawater itself is a strong electrolyte with a high salt content. This makes the corrosion rate of metals in seawater much higher than that in terrestrial environments. Chloride ions in seawater can penetrate the oxide film on the metal surface, react chemically with the metal, and form corrosion products. In addition, the impact of waves, the rise and fall of tides, and the action of ocean currents will cause mechanical wear on marine engineering facilities, further aggravating the degree of corrosion.
[0004] Temperature and pressure are also important factors affecting marine corrosion. In deep-sea environments, the temperature and pressure of seawater change with increasing depth. Low temperature and high pressure affect the corrosion behavior of metals, making the corrosion process more complicated. For example, on deep-sea oil drilling platforms, steel structures are in a high-pressure, low-temperature seawater environment for a long time, which is prone to serious corrosion problems such as stress corrosion cracking.
[0005] The attachment of marine organisms is also a major problem faced by marine engineering. Various organisms in the ocean, such as shellfish, algae, barnacles, etc., will attach and grow on the surface of marine engineering facilities. The attachment of these organisms will not only increase the weight and resistance of the facilities, affecting their normal operation, but also form biofilms, providing a favorable environment for corrosion. The metabolic activities of microorganisms in the biofilm will produce acidic substances, which will accelerate the corrosion of metals.
[0006] Faced with such severe marine corrosion problems, marine engineering anti-corrosion coatings have become an important means of protecting marine engineering facilities. Anti-corrosion coatings form a dense protective film on the metal surface to prevent seawater, oxygen and other corrosive media from contacting the metal, thereby achieving the purpose of corrosion prevention. This protective film can be a physical isolation layer or a stable compound layer formed by chemical reaction.
[0007] Early marine engineering anti-corrosion coatings mainly used materials such as asphalt and tar. Although they have certain anti-corrosion effects, they have serious environmental pollution and short service life. Therefore, it is necessary to continuously develop new marine engineering anti-corrosion coatings to better improve adhesion, chemical corrosion resistance, weather resistance and wear resistance, better protect marine engineering facilities and extend their service life. Summary of the invention
[0008] The existing coatings for marine engineering equipment have problems in that their corrosion resistance cannot meet the requirements for longer-term use, and their corrosion resistance against strong electrolytes, temperature, pressure, marine organisms, etc. is still relatively poor. The present invention provides a marine engineering anti-corrosion coating and a preparation method thereof. The raw materials of the coating include fluorocarbon resin, modified synthetic mica, modified basalt fiber, modified carbon nanotube, nano-silicon dioxide, nano-zinc oxide, nano-titanium dioxide, carbon fiber, zinc phosphate, terminal hydroxyl polybutadiene, plant extract, organic tin, fluorine-modified acrylic leveling agent, silicone defoaming agent, butyl acetate and other ingredients; the ingredients are used in a certain proportion, and have the advantages of excellent corrosion resistance, good mechanical properties, outstanding anti-aging performance, environmental protection performance and the like. The specific technical scheme is as follows:
[0009] A marine engineering anticorrosive coating, the coating comprising the following raw materials in parts by mass: 40 to 50 parts of fluorocarbon resin, 5 to 10 parts of modified synthetic mica, 3 to 5 parts of modified basalt fiber, 1 to 3 parts of modified carbon nanotubes, 5 to 8 parts of nano silicon dioxide, 1 to 3 parts of nano zinc oxide, 3 to 5 parts of nano titanium dioxide, 3 to 5 parts of carbon fiber, 10 to 15 parts of zinc phosphate, 2 to 4 parts of terminal hydroxyl polybutadiene, 2 to 5 parts of plant extract, 1 to 3 parts of organic tin, 0.5 to 1 part of fluorine-modified acrylate leveling agent, 0.5 to 1 part of silicone defoaming agent and 20 to 30 parts of butyl acetate.
[0010] In the above-mentioned coating, the preparation method of the modified synthetic mica comprises the following steps: according to the mass ratio, ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate = 100: (3-5): (1-3): (0.5-1), mixing and preparing to obtain modified liquid I; according to the mass ratio, modified liquid I: synthetic mica = 100: (15-20), adding synthetic mica to the modified liquid I, mixing, distilling to recover ethanol, drying, and breaking up to obtain modified synthetic mica.
[0011] In the preparation method of the modified synthetic mica, the synthetic mica is fluorphlogopite, and the particle size of the synthetic mica is through a 325-mesh sieve; the mixing is ultrasonic mixing, the frequency of the ultrasonic mixing is 30kHz to 40kHz, and the time of the ultrasonic mixing is 10min to 30min.
[0012] In the above-mentioned coating, the preparation method of the modified basalt fiber includes the following steps: according to the mass ratio, water: sodium stannate: polyvinyl alcohol: sodium hexametaphosphate = 100: (3-5): (0.5-1): (0.5-1), mixing and preparing to obtain modified liquid II; according to the mass ratio, modified liquid II: basalt fiber = 150: (10-15), adding basalt fiber to modified liquid II, mixing, distilling and recovering water, drying, and breaking up to obtain modified basalt fiber.
[0013] In the preparation method of the modified basalt fiber, the diameter of the basalt fiber is below 15 μm, and the length of the basalt fiber is 0.5 mm to 1.5 mm; the mixing is ultrasonic mixing, the frequency of the ultrasonic mixing is 30 kHz to 40 kHz, and the time of the ultrasonic mixing is 10 min to 30 min.
[0014] In the above-mentioned coating, the preparation method of the modified carbon nanotubes includes the following steps: according to the mass ratio, ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate = 100: (1-3): (1-3): (0.5-1), mixing and preparing to obtain modified liquid III; according to the mass ratio, modified liquid III: carbon nanotubes = 150: (10-15), adding carbon nanotubes to the modified liquid III, mixing, distilling to recover ethanol, drying, and breaking up to obtain modified carbon nanotubes.
[0015] In the above-mentioned preparation method of modified carbon nanotubes, the particle size range of the carbon nanotubes is below 100 nm; the mixing is ultrasonic mixing, the frequency of ultrasonic mixing is 30 kHz to 40 kHz, and the time of ultrasonic mixing is 20 min to 50 min.
[0016] In the above-mentioned coating, the preparation method of the plant extract comprises the following steps: according to the mass ratio of Kandelia kandelii leaves:Magnolia officinalis leaves=(5-10):(1-3), Kandelia kandelii leaves andMagnolia officinalis leaves are mixed and crushed to obtain a mixture, 6 to 8 times the mass of ethanol of the mixture is used for percolation extraction to obtain an leaching solution, ethanol is recovered by distillation, and the plant extract is obtained after drying and dispersion.
[0017] In the above coating, the particle size range of the nano silicon dioxide is below 100nm; the particle size range of the nano zinc oxide is below 100nm; the particle size range of the nano titanium dioxide is below 100nm; the diameter range of the carbon fiber is below 10μm, and the length is 0.5mm to 1.5mm; the particle size range of the zinc phosphate is below 5μm.
[0018] The above-mentioned method for preparing the marine engineering anti-corrosion coating comprises the following steps:
[0019] S1: Mix nano silicon dioxide, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions, then add carbon fiber and zinc phosphate, and mix them by air flow to obtain a mixture A;
[0020] S2: According to the mass proportions, butyl acetate and mixture A are mixed evenly at a high speed of 1000 r / min to 1500 r / min, and then fluorocarbon resin, terminal hydroxy polybutadiene, fluorine-modified acrylate leveling agent and silicone defoaming agent are added and mixed evenly, and then plant extracts and organotin are added and mixed evenly, and finally modified synthetic mica, modified basalt fiber and modified carbon nanotubes are added, and mixed at a low speed of 300 r / min to 500 r / min for 30 min to 50 min to obtain a coating.
[0021] The present invention provides an anti-corrosion coating for marine engineering and a preparation method thereof, and the beneficial effects are as follows:
[0022] 1. The raw materials of the marine engineering anticorrosive coating of the present invention include fluorocarbon resin, modified synthetic mica, modified basalt fiber, modified carbon nanotube, nano silicon dioxide, nano zinc oxide, nano titanium dioxide, carbon fiber, zinc phosphate, terminal hydroxyl polybutadiene, plant extract, organic tin, fluorine-modified acrylate leveling agent, organic silicon defoamer and butyl acetate. The components are used in a certain proportion, and have the advantages of excellent anticorrosion performance, good mechanical properties, outstanding anti-aging performance, environmental protection performance and the like.
[0023] Modified synthetic mica, modified basalt fiber, modified carbon nanotubes with nano-size effect, nano-silica and other ingredients cooperate with each other to form a complex physical barrier structure in the coating. This structure can greatly extend the path for corrosive substances (such as chloride ions in seawater and salt spray) to penetrate into the metal substrate, effectively prevent the invasion of corrosive media, and slow down the corrosion rate of the metal. The zinc phosphate component can react with the metal substrate in the coating to form a dense phosphating film corrosion inhibition layer, which prevents corrosive substances from contacting the metal and plays a role in corrosion inhibition. Fluorocarbon resin, organic tin and other ingredients also have certain anti-corrosion properties, and synergize with zinc phosphate to further enhance the anti-corrosion ability of the coating and effectively respond to the long-term corrosion challenges in the marine environment. Carbon fiber has high tensile strength and modulus, which can provide a strong reinforcement effect for the coating and improve the overall strength of the coating; terminal hydroxyl polybutadiene has a certain flexibility. When combined with carbon fiber, the coating can maintain a high strength while having good toughness, and can withstand various mechanical stresses caused by wave scouring, current friction, and object collision in the marine environment, and is not prone to cracking, breakage and other problems. The addition of modified basalt fiber and nano-silica can improve the hardness and wear resistance of the coating. In marine engineering, the coating is often subjected to friction and wear from seawater, sea sand, and marine organisms. The synergistic effect of these components can reduce the wear of the coating and extend the service life of the coating.
[0024] Fluorocarbon resin itself has excellent weather resistance and can be exposed to the marine environment for a long time without aging, powdering, cracking, etc. Ingredients such as nano-titanium dioxide and nano-zinc oxide work synergistically with fluorocarbon resin to further improve the weather resistance of the coating and ensure that the coating maintains good performance in the long-term marine environment.
[0025] Plant extracts combined with a small amount of nano zinc oxide and organic tin have a good inhibitory effect on bacteria, algae and other microorganisms in the ocean, and have a repellent effect on marine life, which can prevent marine life from attaching and growing on the coating surface. The attachment of marine life not only affects the appearance of the coating, but also leads to increased local corrosion. The combined use of these ingredients can effectively reduce the damage of biological fouling to the coating and maintain the anti-corrosion performance of the coating. The addition of natural ingredients such as plant extracts can reduce environmental pollution to a certain extent and make the coating more environmentally friendly.
[0026] Second, the present invention adopts ethanol, pentaerythritol stearate, cellulose nitrate, sodium hexametaphosphate to prepare the modification liquid, and performs surface modification on synthetic mica. Pentaerythritol stearate improves the mutual fusion of synthetic mica and other components in the coating. In the coating system, good compatibility can ensure that the modified synthetic mica is evenly dispersed and avoids agglomeration, thereby making the performance of the coating more stable. Pentaerythritol stearate helps to improve the binding force between synthetic mica and organic resin (such as fluorocarbon resin, terminal hydroxyl polybutadiene, etc.), so that when the coating is subjected to external force or corrosive medium, the synthetic mica can better play its barrier and reinforcement role, thereby improving the overall anti-corrosion performance of the coating. Cellulose nitrate can form a layer of organic film on the surface of synthetic mica, increasing the lipophilicity of synthetic mica. In marine engineering anticorrosive coatings, most of the components are organic substances. The improvement of lipophilicity makes it easier for synthetic mica to interact with these organic components, further enhancing its compatibility with the coating system. It can also adjust the surface polarity of synthetic mica to make it have a closer surface energy with other components in the coating, thereby promoting uniform mixing between the components and improving the overall performance of the coating. Sodium hexametaphosphate can prevent the aggregation of synthetic mica particles during the modification process and ensure that the synthetic mica can be evenly dispersed in the modified liquid.
[0027] The modified synthetic mica can better form a layered barrier structure in the coating. Due to its improved compatibility with the coating system, the modified synthetic mica can be arranged more closely in the coating, making the diffusion, penetration and migration paths of corrosive substances in the paint film more complex and tortuous. This greatly slows down the progress of corrosion and enhances the coating's resistance to corrosive media such as seawater and salt spray. The modified synthetic mica can work synergistically with other anti-corrosion ingredients to jointly build a more solid anti-corrosion barrier, providing more effective protection for metal substrates in marine engineering. The modified synthetic mica is more firmly combined with the coating system and can better withstand friction when the coating is worn. Its higher hardness and mechanical strength can effectively resist the wear caused by wave scouring, ocean current friction, etc., extend the service life of the coating, and thus maintain the long-term stability of the coating's anti-corrosion performance.
[0028] 3. The present invention uses water, sodium stannate, polyvinyl alcohol, and sodium hexametaphosphate to prepare a modification liquid to modify basalt fiber. Sodium stannate can form a chemical bonding layer on the surface of basalt fiber, change the surface properties of the fiber, and make it easier to interact with the organic components in the coating. This helps to improve the dispersibility of basalt fiber in the coating and avoid the occurrence of agglomeration, so that the performance of the coating is more uniform and stable; it can enhance the binding force between basalt fiber and the main components of the coating such as fluorocarbon resin and terminal hydroxyl polybutadiene, form a more solid structure in the coating system, and improve the overall strength and stability of the coating. Polyvinyl alcohol has good hydrophilicity and adhesion, and can form a protective film on the surface of basalt fiber, which makes the modified basalt fiber easier to disperse and combine in the water-based coating system, improves the construction performance and coating quality of the coating; it can also cross-link with other components in the coating to form a tighter network structure, and enhance the mechanical properties and corrosion resistance of the coating. Sodium hexametaphosphate can effectively prevent basalt fiber from agglomerating during the modification process, ensuring that the fiber is evenly dispersed in the modification liquid.
[0029] The modified basalt fiber has higher tensile strength and elastic modulus, which can significantly enhance the overall strength and toughness of the coating. In marine engineering, the coating needs to withstand various mechanical stresses such as wave impact and current friction. The addition of modified basalt fiber can improve the impact resistance and tensile resistance of the coating, making it more durable; the reinforcement of the fiber can also reduce the cracks and damage of the coating when it is subjected to external forces, and extend the service life of the coating. Basalt fiber itself has a certain corrosion resistance. After modification, its corrosion resistance is further improved. The modified fiber can synergize with other anti-corrosion components in the coating to form a more effective anti-corrosion barrier to prevent corrosive media such as seawater and salt spray from corroding the metal substrate. Good corrosion resistance can ensure that the coating maintains stable performance for a long time in the marine environment and provide reliable protection for marine engineering facilities. Due to the improved compatibility of the modified basalt fiber with the coating system, it is easier to disperse evenly during the coating production process, reducing the time and difficulty of stirring and mixing. This not only improves production efficiency, but also reduces energy consumption.
[0030] Fourth, the present invention uses ethanol, pentaerythritol stearate, cellulose nitrate, and sodium hexametaphosphate to prepare a modification liquid to modify carbon nanotubes. Pentaerythritol stearate helps carbon nanotubes to be evenly dispersed in the coating and avoid agglomeration, thereby making the performance of the coating more stable; it can improve the binding force between carbon nanotubes and resins such as fluorocarbon resins and terminal hydroxyl polybutadiene, and enhance the overall strength and toughness of the coating. Cellulose nitrate forms an organic film on the surface of carbon nanotubes to increase their lipophilicity. In marine engineering anticorrosive coatings, most of the components are organic substances. The improvement of lipophilicity makes it easier for carbon nanotubes to interact with these organic components, further enhancing the compatibility with the coating system; it can adjust the surface polarity of carbon nanotubes so that they have a closer surface energy to other components in the coating, and promote uniform mixing between the components. Sodium hexametaphosphate can prevent carbon nanotubes from agglomerating during the modification process, and can also improve the stability of carbon nanotubes in the coating, avoiding problems such as precipitation and stratification during storage and use.
[0031] The modified carbon nanotubes can better form a conductive network. In the coating, the electrons generated by the anode can be smoothly conducted to the surface of the coating through the carbon nanotube network, so that the cathode reaction and reaction products of electrochemical corrosion are transferred from the surface of the steel substrate to the surface of the anti-corrosion coating, effectively reducing the accumulation of corrosion products on the surface of the substrate, inhibiting the blistering and shedding of the coating, and improving the durability of the coating adhesion. Good conductivity can also improve the antistatic properties of the coating and reduce the damage of static electricity accumulation to the coating and the metal substrate. Carbon nanotubes have extremely high strength and modulus. After modification, they can more effectively enhance the strength, hardness and wear resistance of the coating. In the marine environment, the coating needs to withstand various mechanical stresses such as wave scouring and current friction. The addition of modified carbon nanotubes can make the coating more durable. The nano-size effect and high specific surface area carbon nanotubes can synergize with other ingredients in the coating to further improve the overall mechanical properties of the coating. The modified carbon nanotubes have improved compatibility with the coating system, making it easier to disperse evenly during the coating production process, reducing the time and difficulty of stirring and mixing. This improves production efficiency and reduces energy consumption.
[0032] 5. The plant extract is the ethanol percolation extract of the leaves of Kandelia candel and Magnolia officinalis. The various bioactive ingredients contained in the leaves of Kandelia candel and Magnolia officinalis have certain anti-corrosion properties. These ingredients can inhibit the growth of microorganisms in the marine environment and reduce the erosion of metal substrates by bacteria, fungi, etc. Compared with traditional chemical anti-corrosion ingredients, plant extracts are naturally derived and more environmentally friendly, meeting the needs of modern marine engineering for environmentally friendly coatings. Plant extracts cooperate with other anti-corrosion ingredients in the coating, such as fluorocarbon resins and zinc phosphate, to synergistically play an anti-corrosion role. They can prevent the occurrence of corrosion from different angles, jointly build a solid anti-corrosion barrier, and improve the overall anti-corrosion performance of the coating. By inhibiting the growth of microorganisms, plant extracts can keep the coating surface relatively clean and reduce the accumulation of dirt and biological deposits. This helps to reduce the risk of corrosion and extend the service life of the coating. Plant extracts are extracted from natural plants, do not contain harmful chemicals, and have less harm to the environment and human health. The use of anti-corrosion coatings containing plant extracts in marine engineering can reduce pollution to the marine ecological environment.
[0033] 6. In the preparation method of the coating, it is designed to add modified synthetic mica, modified basalt fiber and modified carbon nanotubes at the end, and mix them at a low speed of 300r / min to 500r / min. While ensuring uniform dispersion, it can protect the special structure to the maximum extent and exert the best performance. The low-speed mixing avoids premature damage to the structure of modified synthetic mica, modified basalt fiber and modified carbon nanotubes, better exerts the reinforcing effect, and improves the anti-corrosion performance and adhesion durability of the coating. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0035] Example 1
[0036] A marine engineering anti-corrosion coating, the coating comprising the following raw materials in parts by mass: 45 parts of fluorocarbon resin, 8 parts of modified synthetic mica, 4 parts of modified basalt fiber, 2 parts of modified carbon nanotubes, 6.5 parts of nano silicon dioxide, 2 parts of nano zinc oxide, 4 parts of nano titanium dioxide, 4 parts of carbon fiber, 13 parts of zinc phosphate, 3 parts of terminal hydroxyl polybutadiene, 3 parts of plant extract, 2 parts of organic tin, 0.8 parts of fluorine-modified acrylate leveling agent, 0.8 parts of silicone defoaming agent and 25 parts of butyl acetate.
[0037] Among them, the preparation method of modified synthetic mica includes the following steps: mixing ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate in a mass ratio of 100:4:2:0.8 to obtain modified liquid I; adding synthetic mica to modified liquid I in a mass ratio of 100:18, ultrasonically mixing at 35kHz for 20 minutes, distilling to recover ethanol, drying and breaking up to obtain modified synthetic mica.
[0038] Among them, the preparation method of modified basalt fiber includes the following steps: mixing and preparing modified liquid II in a mass ratio of water: sodium stannate: polyvinyl alcohol: sodium hexametaphosphate = 100:4:0.7:0.8; adding basalt fiber to modified liquid II in a mass ratio of modified liquid II: basalt fiber = 150:13, mixing ultrasonically at 35kHz for 20 minutes, distilling and recovering water, drying and breaking up to obtain modified basalt fiber.
[0039] Among them, the preparation method of modified carbon nanotubes includes the following steps: mixing ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate in a mass ratio of 100:2:2:0.7 to obtain modified liquid III; adding carbon nanotubes to modified liquid III in a mass ratio of 150:13, ultrasonically mixing at 35kHz for 30 minutes, distilling and recovering ethanol, and obtaining modified carbon nanotubes after drying and breaking up.
[0040] The preparation method of the plant extract includes the following steps: mixing and crushing the leaves of Kandelia kandelii and the leaves of Magnolia officinalis in a mass ratio of 7.5:2 to obtain a mixture, performing percolation extraction with ethanol 7 times the mass of the mixture to obtain an extract, distilling and recovering the ethanol, and drying and breaking up to obtain the plant extract.
[0041] The above-mentioned method for preparing the marine engineering anti-corrosion coating comprises the following steps:
[0042] S1: Mix nano silicon dioxide, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions, then add carbon fiber and zinc phosphate, and mix them by air flow to obtain a mixture A;
[0043] S2: According to the mass proportions, butyl acetate and mixture A are mixed evenly at a high speed of 1200 r / min, and then fluorocarbon resin, terminal hydroxy polybutadiene, fluorine-modified acrylate leveling agent and silicone defoaming agent are added and mixed evenly, and then plant extract and organotin are added and mixed evenly, and finally modified synthetic mica, modified basalt fiber and modified carbon nanotubes are added, and mixed at a low speed of 400 r / min for 40 minutes to obtain a coating.
[0044] Example 2
[0045] A marine engineering anti-corrosion coating, the coating comprising the following raw materials in parts by mass: 40 parts of fluorocarbon resin, 5 parts of modified synthetic mica, 3 parts of modified basalt fiber, 1 part of modified carbon nanotube, 5 parts of nano silicon dioxide, 1 part of nano zinc oxide, 3 parts of nano titanium dioxide, 3 parts of carbon fiber, 10 parts of zinc phosphate, 2 parts of terminal hydroxyl polybutadiene, 2 parts of plant extract, 1 part of organic tin, 0.5 parts of fluorine-modified acrylate leveling agent, 0.5 parts of silicone defoaming agent and 20 parts of butyl acetate.
[0046] Among them, the preparation method of modified synthetic mica includes the following steps: mixing ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate in a mass ratio of 100:3:1:0.5 to obtain modified liquid I; adding synthetic mica to modified liquid I in a mass ratio of 100:15, ultrasonically mixing at 30kHz for 10 minutes, distilling to recover ethanol, drying and breaking up to obtain modified synthetic mica.
[0047] Among them, the preparation method of modified basalt fiber includes the following steps: mixing and preparing modified liquid II at a mass ratio of water: sodium stannate: polyvinyl alcohol: sodium hexametaphosphate = 100:3:0.5:0.5; adding basalt fiber to modified liquid II at a mass ratio of modified liquid II: basalt fiber = 150:10, mixing ultrasonically at 30kHz for 10 minutes, distilling and recovering water, drying and breaking up to obtain modified basalt fiber.
[0048] Among them, the preparation method of modified carbon nanotubes includes the following steps: mixing ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate in a mass ratio of 100:1:1:0.5 to obtain modified liquid III; adding carbon nanotubes to modified liquid III in a mass ratio of modified liquid III: carbon nanotubes in a mass ratio of 150:10, mixing ultrasonically at 30kHz for 20 minutes, distilling and recovering ethanol, and obtaining modified carbon nanotubes after drying and breaking up.
[0049] The preparation method of the plant extract includes the following steps: mixing and crushing the leaves of Kandelia kandelii and the leaves of Magnolia officinalis in a mass ratio of 5:1 to obtain a mixture, using ethanol 6 times the mass of the mixture for percolation extraction to obtain an extract, distilling to recover the ethanol, and drying and breaking up to obtain the plant extract.
[0050] The above-mentioned method for preparing the marine engineering anti-corrosion coating comprises the following steps:
[0051] S1: Mix nano silicon dioxide, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions, then add carbon fiber and zinc phosphate, and mix them by air flow to obtain a mixture A;
[0052] S2: According to the mass proportions, butyl acetate and mixture A are mixed evenly at a high speed of 1000 r / min, and then fluorocarbon resin, terminal hydroxy polybutadiene, fluorine-modified acrylate leveling agent and silicone defoaming agent are added and mixed evenly, and then plant extract and organotin are added and mixed evenly, and finally modified synthetic mica, modified basalt fiber and modified carbon nanotubes are added and mixed at a low speed of 300 r / min for 30 minutes to obtain a coating.
[0053] Example 3
[0054] A marine engineering anti-corrosion coating, the coating comprising the following raw materials in parts by mass: 42 parts of fluorocarbon resin, 6 parts of modified synthetic mica, 3.5 parts of modified basalt fiber, 1.5 parts of modified carbon nanotubes, 6 parts of nano silicon dioxide, 1.5 parts of nano zinc oxide, 3.5 parts of nano titanium dioxide, 3.5 parts of carbon fiber, 12 parts of zinc phosphate, 2.5 parts of terminal hydroxyl polybutadiene, 3 parts of plant extract, 1.5 parts of organic tin, 0.6 parts of fluorine-modified acrylate leveling agent, 0.6 parts of silicone defoaming agent and 22 parts of butyl acetate.
[0055] Among them, the preparation method of modified synthetic mica includes the following steps: according to the mass ratio, ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate = 100:3.5:1.5:0.6, mix and prepare to obtain modified liquid I; according to the mass ratio, modified liquid I: synthetic mica = 100:16, add synthetic mica to modified liquid I, mix ultrasonically at 30kHz for 15 minutes, distill and recover ethanol, dry and disperse, and obtain modified synthetic mica.
[0056] Among them, the preparation method of modified basalt fiber includes the following steps: mixing and preparing modified liquid II according to the mass ratio of water: sodium stannate: polyvinyl alcohol: sodium hexametaphosphate = 100:3.5:0.6:0.6; adding basalt fiber to modified liquid II according to the mass ratio of modified liquid II: basalt fiber = 150:11, mixing ultrasonically at 30kHz for 15 minutes, distilling and recovering water, drying and breaking up to obtain modified basalt fiber.
[0057] Among them, the preparation method of modified carbon nanotubes includes the following steps: mixing ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate in a mass ratio of 100:1.5:1.5:0.6 to obtain modified liquid III; adding carbon nanotubes to modified liquid III in a mass ratio of 150:11 to carbon nanotubes, mixing at 30kHz ultrasonically for 30 minutes, distilling and recovering ethanol, and obtaining modified carbon nanotubes after drying and breaking up.
[0058] The preparation method of the plant extract includes the following steps: mixing and crushing the leaves of Kandelia kandelii and the leaves of Magnolia officinalis in a mass ratio of 6:1.5 to obtain a mixture, using 6.5 times the mass of ethanol of the mixture for percolation extraction to obtain an extract, distilling to recover the ethanol, and drying and breaking up to obtain the plant extract.
[0059] The above-mentioned method for preparing the marine engineering anti-corrosion coating comprises the following steps:
[0060] S1: Mix nano silicon dioxide, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions, then add carbon fiber and zinc phosphate, and mix them by air flow to obtain a mixture A;
[0061] S2: According to the mass proportions, butyl acetate and mixture A are mixed evenly at a high speed of 1000 r / min, and then fluorocarbon resin, terminal hydroxy polybutadiene, fluorine-modified acrylate leveling agent and silicone defoaming agent are added and mixed evenly, and then plant extract and organotin are added and mixed evenly, and finally modified synthetic mica, modified basalt fiber and modified carbon nanotubes are added, and mixed at a low speed of 350 r / min for 35 minutes to obtain a coating.
[0062] Example 4
[0063] A marine engineering anti-corrosion coating, the coating comprising the following raw materials in parts by mass: 48 parts of fluorocarbon resin, 9 parts of modified synthetic mica, 4.5 parts of modified basalt fiber, 2.5 parts of modified carbon nanotubes, 7 parts of nano silicon dioxide, 2.5 parts of nano zinc oxide, 4.5 parts of nano titanium dioxide, 4 parts of carbon fiber, 13 parts of zinc phosphate, 3.5 parts of terminal hydroxyl polybutadiene, 4.5 parts of plant extract, 2.5 parts of organotin, 0.8 parts of fluorine-modified acrylate leveling agent, 0.8 parts of silicone defoaming agent and 28 parts of butyl acetate.
[0064] Among them, the preparation method of modified synthetic mica includes the following steps: according to the mass ratio, ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate = 100:4.5:2.5:0.8, mix and prepare to obtain modified liquid I; according to the mass ratio, modified liquid I: synthetic mica = 100:19, add synthetic mica to modified liquid I, ultrasonically mix at 40kHz for 25 minutes, distill and recover ethanol, dry and disperse, and obtain modified synthetic mica.
[0065] Among them, the preparation method of modified basalt fiber includes the following steps: mixing and preparing modified liquid II according to the mass ratio of water: sodium stannate: polyvinyl alcohol: sodium hexametaphosphate = 100:4.5:0.8:0.8; adding basalt fiber to modified liquid II according to the mass ratio of modified liquid II: basalt fiber = 150:13, mixing ultrasonically at 40kHz for 25 minutes, distilling and recovering water, drying and breaking up to obtain modified basalt fiber.
[0066] Among them, the preparation method of modified carbon nanotubes includes the following steps: mixing ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate in a mass ratio of 100:2.5:2.5:0.8 to obtain modified liquid III; adding carbon nanotubes to modified liquid III in a mass ratio of 150:13 to carbon nanotubes, mixing at 40kHz ultrasonically for 45 minutes, distilling and recovering ethanol, and obtaining modified carbon nanotubes after drying and breaking up.
[0067] The preparation method of the plant extract includes the following steps: mixing and crushing the leaves of Kandelia ovata and the leaves of Magnolia officinalis in a mass ratio of 9:2.5 to obtain a mixture, using 7.5 times the mass of ethanol of the mixture for percolation extraction to obtain an extract, distilling to recover the ethanol, and drying and breaking up to obtain the plant extract.
[0068] The above-mentioned method for preparing the marine engineering anti-corrosion coating comprises the following steps:
[0069] S1: Mix nano silicon dioxide, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions, then add carbon fiber and zinc phosphate, and mix them by air flow to obtain a mixture A;
[0070] S2: According to the mass proportions, butyl acetate and mixture A are mixed evenly at a high speed of 1400 r / min, and then fluorocarbon resin, terminal hydroxy polybutadiene, fluorine-modified acrylate leveling agent and silicone defoaming agent are added and mixed evenly, and then plant extracts and organotin are added and mixed evenly, and finally modified synthetic mica, modified basalt fiber and modified carbon nanotubes are added, and mixed at a low speed of 450 r / min for 45 minutes to obtain a coating.
[0071] Example 5
[0072] A marine engineering anti-corrosion coating, the coating comprising the following raw materials in parts by mass: 50 parts of fluorocarbon resin, 10 parts of modified synthetic mica, 5 parts of modified basalt fiber, 3 parts of modified carbon nanotubes, 8 parts of nano silicon dioxide, 3 parts of nano zinc oxide, 5 parts of nano titanium dioxide, 5 parts of carbon fiber, 15 parts of zinc phosphate, 4 parts of terminal hydroxyl polybutadiene, 5 parts of plant extract, 3 parts of organic tin, 1 part of fluorine-modified acrylate leveling agent, 1 part of silicone defoaming agent and 30 parts of butyl acetate.
[0073] Among them, the preparation method of modified synthetic mica includes the following steps: according to the mass ratio, ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate = 100:5:3:1, mixing and preparing to obtain modified liquid I; according to the mass ratio, modified liquid I: synthetic mica = 100:20, adding synthetic mica to modified liquid I, 40kHz ultrasonic mixing for 30 minutes, distilling to recover ethanol, drying and breaking up, to obtain modified synthetic mica.
[0074] Among them, the preparation method of modified basalt fiber includes the following steps: mixing and preparing modified liquid II at a mass ratio of water: sodium stannate: polyvinyl alcohol: sodium hexametaphosphate = 100:5:1:1; adding basalt fiber to modified liquid II at a mass ratio of modified liquid II: basalt fiber = 150:15, mixing ultrasonically at 40kHz for 30 minutes, distilling and recovering water, drying and breaking up to obtain modified basalt fiber.
[0075] Among them, the preparation method of modified carbon nanotubes includes the following steps: mixing ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate in a mass ratio of 100:3:3:1 to obtain modified liquid III; adding carbon nanotubes to modified liquid III in a mass ratio of 150:15 to carbon nanotubes, mixing ultrasonically at 40kHz for 50 minutes, distilling and recovering ethanol, and obtaining modified carbon nanotubes after drying and breaking up.
[0076] The preparation method of the plant extract includes the following steps: mixing and crushing the Kandelia kandelii leaves and the Magnolia officinalis leaves in a mass ratio of 10:3 to obtain a mixture, using 8 times the mass of ethanol to perform percolation extraction to obtain an extract, distilling to recover the ethanol, and drying and breaking up to obtain the plant extract.
[0077] The above-mentioned method for preparing the marine engineering anti-corrosion coating comprises the following steps:
[0078] S1: Mix nano silicon dioxide, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions, then add carbon fiber and zinc phosphate, and mix them by air flow to obtain a mixture A;
[0079] S2: According to the mass proportions, butyl acetate and mixture A are mixed evenly at a high speed of 1500r / min, and then fluorocarbon resin, terminal hydroxy polybutadiene, fluorine-modified acrylate leveling agent and silicone defoaming agent are added and mixed evenly, and then plant extract and organotin are added and mixed evenly, and finally modified synthetic mica, modified basalt fiber and modified carbon nanotubes are added, and mixed at a low speed of 500r / min for 50min to obtain a coating.
[0080] In the above embodiments, the synthetic mica used is fluorphlogopite, and the particle size of the synthetic mica is through a 325 mesh sieve; the diameter range of the basalt fiber is less than 15 μm, and the length range of the basalt fiber is 0.5 mm to 1.5 mm; the particle size range of the carbon nanotube is less than 100 nm; the particle size range of nano-silicon dioxide is less than 100 nm; the particle size range of nano-zinc oxide is less than 100 nm; the particle size range of nano-titanium dioxide is less than 100 nm; the diameter range of the carbon fiber is less than 10 μm, and the length is 0.5 mm to 1.5 mm; the particle size range of zinc phosphate is less than 5 μm.
[0081] The model of fluorocarbon resin is HLR-2, which comes from Jinan Shenglong Chemical Co., Ltd. Fluorphlogopite comes from Hebei Jinghang Mineral Products Co., Ltd. The model of pentaerythritol stearate is PETS-1, which comes from Hai'an Petrochemical Plant in Jiangsu Province. Cellulose nitrate comes from Maoming Petrochemical. The model of polyvinyl alcohol is 2488, which comes from Zhengzhou Xinke Chemical Products Co., Ltd. Organic tin comes from Shandong Maofa Chemical Co., Ltd. The terminal hydroxyl polybutadiene is II model-hydroxyl value (0.54-0.64), which comes from Shenzhen Hongyuan Chemical New Materials Technology Co., Ltd. The model of fluorine-modified acrylate leveling agent is LS3024, which comes from Kunshan Loris Polymer Materials Co., Ltd. The model of silicone defoamer is CI-0560, which comes from Guangdong Nanhui New Materials Co., Ltd.
[0082] Comparative Example 1
[0083] In the coating, the modified synthetic mica is replaced by synthetic mica; other parameters and methods are the same as in Example 1.
[0084] Comparative Example 2
[0085] In the coating, the modified basalt fiber is replaced by basalt fiber; other parameters and methods are the same as in Example 1.
[0086] Comparative Example 3
[0087] In the coating, the modified carbon nanotubes are replaced by carbon nanotubes; other parameters and methods are the same as in Example 1.
[0088] Comparative Example 4
[0089] In the coating, the modified synthetic mica is replaced by synthetic mica, the modified basalt fiber is replaced by basalt fiber, and the modified carbon nanotube is replaced by carbon nanotube; other parameters and methods are the same as in Example 1.
[0090] Comparative Example 5
[0091] In the preparation method of the plant extract, no Kandelia candel leaves are added; other parameters and methods are the same as those in Example 1.
[0092] Comparative Example 6
[0093] In the preparation method of the plant extract, Magnolia officinalis leaf is not added; other parameters and methods are the same as in Example 1.
[0094] Comparative Example 7
[0095] No plant extract is added to the coating, and the content of the plant extract is replaced by butyl acetate; other parameters and methods are the same as in Example 1.
[0096] The coatings prepared in the above-mentioned embodiments and comparative examples were tested for their performance.
[0097] Test plate: the substrate is a bottom carbon steel plate, the coating thickness is 180 μm, and the coatings are the coatings prepared in the above embodiments and comparative examples.
[0098] (1) Adhesion test: The test was conducted according to the test method of GB / T 5210 “Adhesion test for paints and varnishes by pull-off method”. The test results are shown in Table 1.
[0099] (2) Salt spray resistance test: According to the test method of GB / T 1771 "Determination of neutral salt spray resistance of paints and varnishes", the coated test panel is placed on the sample rack of the salt spray test chamber and subjected to a neutral salt spray test (sodium chloride solution concentration of 5%, test temperature of 35±2℃, salt spray deposition rate of 1.5ml / 80cm 2 / h), and after continuous spraying for 1000h, the state of the coating was observed. The measurement results are shown in Table 1.
[0100] Salt spray resistance evaluation level, level 10: no coating defect area, no change in the appearance of the test plate surface; level 9: the coating defect area accounts for no more than 0.1%, and the test plate surface has slight to moderate discoloration; level 8: the coating defect area accounts for greater than or equal to 0.1% and less than 0.25%, the test plate surface is seriously discolored or has very slight corrosion products; level 7: the coating defect area accounts for greater than or equal to 0.25% and less than 0.5%, the test plate surface is seriously glossy or has very slight corrosion products; level 6: the coating defect area accounts for greater than or equal to 0.5% and less than 1.0%, the test plate surface is seriously glossy or there is a thin layer of corrosion products or pitting on the local surface of the test plate; level 5 Level 4: The coating defect area accounts for greater than or equal to 2.5% and less than 5%, and there are corrosion products or pitting on the test plate surface, and one of them is distributed on the entire test plate surface; Level 4: The coating defect area accounts for greater than or equal to 2.5% and less than 5%, and there is a thick corrosion product layer or pitting on the test plate surface; Level 3: The coating defect area accounts for greater than or equal to 5% and less than 10%, and there is a very thick corrosion product layer or pitting on the test plate surface, and there are deep pitting; Level 2: The coating defect area accounts for greater than or equal to 10% and less than 25%, and the test plate has base metal corrosion; Level 1: The coating defect area accounts for greater than or equal to 25% and less than 50%, which is a serious corrosion phenomenon.
[0101] (3) Water resistance test: The test was conducted according to the test method of GB / T 1733 “Determination of water resistance of paint films”. The test panels were placed in water at 25°C for 30 days to observe whether the test panels showed any blistering, peeling or rusting. The water resistance results are shown in Table 1.
[0102] Water resistance evaluation level: excellent: the paint film remains completely original, and there is no gloss loss, color change, blistering, wrinkling, peeling, rust and other phenomena on the paint film; good: the paint film surface has slight changes, such as slight gloss loss and slightly lighter color, but it does not affect the overall performance and appearance of the paint film; medium: the paint film surface has obvious changes, such as obvious gloss loss, color change, blistering, wrinkling, etc., but it has not reached the level of serious damage; very poor: the paint film has serious bubbling, peeling, rust and other phenomena, and the water resistance of the paint film is very poor and cannot meet the use requirements.
[0103] (4) Aging resistance test: According to the xenon lamp aging test in GB / T 1865 "Artificial weathering and artificial radiation exposure of paints and varnishes to filtered xenon arc radiation", the weathering hydrophobicity and weathering adhesion are tested: the test panel is placed in a xenon lamp aging test chamber and the irradiance is controlled at a wavelength of 340nm. The irradiance setting value is 0.5W / m 2 The blackboard temperature is set at 65℃, the temperature in the test box is 50℃ during the light stage; the temperature is 25℃ during the dark stage, and the relative humidity is 60%. The rainfall time is 20min, the rain stop time is 1h, the water spray pressure of the rainfall is controlled at 0.15MPa, and the rainfall water quality is distilled water. The test time is 1000 hours. After aging, the contact angle meter is used to detect the test board coating, and the surface energy change rate is calculated. The radiation weathering surface energy change rate = (surface energy after aging test-initial surface energy after drying) / initial surface energy after drying × 100%; the pull-off method is used to detect the radiation weathering adhesion.
[0104] (5) Flexibility test: The test was conducted according to the test method of GB / T 1731-1993 Determination of paint film flexibility. The coated test panel was placed on a flexibility tester, and pressure was applied to the test panel with an axial rod to bend the test panel. The coating was observed to see if cracks or peeling occurred. The flexibility test results are shown in Table 1.
[0105] Flexibility evaluation level: excellent: the paint film has no damage when bent on a shaft rod with a diameter of 1mm; good: the paint film is intact when bent on a shaft rod with a diameter of 2mm-3mm; medium: the paint film is intact when bent on a shaft rod with a diameter of 4mm-5mm; poor: there are slight signs of damage when bent on a shaft rod with a diameter of 6mm-8mm, and the paint film has slight reticulation or cracks; very poor: the paint film has reticulation, cracks or peeling when bent on a shaft rod with a diameter of more than 8mm.
[0106] Table 1 Coating performance test results
[0107]
[0108]
[0109] From the above results, it can be seen that the anti-corrosion coatings of Examples 1 to 5 have good adhesion, salt spray resistance, water resistance, aging resistance and flexibility. The anti-corrosion coatings form a dense protective film on the metal surface, thereby preventing moisture, oxygen and other corrosive media from contacting the metal, thereby achieving the purpose of anti-corrosion, and can protect marine engineering facilities and extend their service life. From the results of Comparative Examples 1 to 3, it can be seen that when the modified synthetic mica, modified basalt fiber or modified carbon nanotubes are replaced by unmodified materials, the performance indicators of the coating, such as adhesion, salt spray resistance, water resistance, aging resistance and flexibility, all decrease to varying degrees; from the results of Comparative Example 4, it can be seen that when the modified synthetic mica, modified basalt fiber and modified carbon nanotubes are all replaced by unmodified materials, the performance indicators of the coating are greatly reduced. It can be seen that the simultaneous modification of synthetic mica, basalt fiber and carbon nanotubes can greatly improve the corrosion resistance and adhesion of the coating; from the results of Comparative Examples 5 to 7, it can be seen that when no Kandelia candel leaves or Magnolia officinalis leaves are added to the preparation method of the plant extract, or no plant extract is added to the coating, the radiation aging resistance of the coating is reduced, and the adhesion, salt spray resistance, water resistance and flexibility do not change much, and the basic performance of the coating is not affected.
[0110] The test plates of each embodiment and each comparative example were placed in a coastal water, where the seawater contained natural marine organisms such as fish, shellfish, algae, and barnacles. After 60 days, the test plates were taken out to observe the biological attachment and corrosion on the test plate surfaces. The results were as follows: the test plates of embodiments 1 to 5 and the test plates of comparative examples 1 to 4 had no marine biological attachment; the test plates of comparative examples 5 to 7 had marine biological attachment to varying degrees, including bryozoans, seaweed, barnacles, etc., and the amount of marine biological attachment on the test plate of comparative example 7 was the largest, which was greater than the sum of the biological attachment amounts of the test plates of comparative example 5 and comparative example 6.
Claims
1. A marine engineering anticorrosion coating, characterized in that: The coating includes the following raw materials in parts by mass: 40 to 50 parts of fluorocarbon resin, 5 to 10 parts of modified synthetic mica, 3 to 5 parts of modified basalt fiber, 1 to 3 parts of modified carbon nanotubes, 5 to 8 parts of nano-silicon dioxide, 1 to 3 parts of nano-zinc oxide, 3 to 5 parts of nano-titanium dioxide, 3 to 5 parts of carbon fiber, 10 to 15 parts of zinc phosphate, 2 to 4 parts of terminal hydroxyl polybutadiene, 2 to 5 parts of plant extract, 1 to 3 parts of organic tin, 0.5 to 1 part of fluorine-modified acrylate leveling agent, 0.5 to 1 part of silicone defoaming agent and 20 to 30 parts of butyl acetate.
2. The marine engineering anticorrosion coating according to claim 1, characterized in that: The preparation method of the modified synthetic mica comprises the following steps: mixing and preparing a modified liquid I according to a mass ratio of ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate = 100: (3-5): (1-3): (0.5-1); adding the synthetic mica to the modified liquid I according to a mass ratio of modified liquid I: synthetic mica = 100: (15-20), mixing, distilling and recovering ethanol, and drying and breaking up to obtain the modified synthetic mica.
3. The marine engineering anticorrosion coating according to claim 2, characterized in that: The synthetic mica is fluorphlogopite, and the particle size of the synthetic mica is through a 325-mesh sieve; the mixing is ultrasonic mixing, the frequency of the ultrasonic mixing is 30kHz to 40kHz, and the time of the ultrasonic mixing is 10min to 30min.
4. The marine engineering anticorrosion coating according to claim 1, characterized in that: The preparation method of the modified basalt fiber comprises the following steps: mixing and preparing a modified liquid II according to a mass ratio of water: sodium stannate: polyvinyl alcohol: sodium hexametaphosphate = 100: (3-5): (0.5-1): (0.5-1); adding the basalt fiber to the modified liquid II according to a mass ratio of modified liquid II: basalt fiber = 150: (10-15), mixing, distilling and recovering water, drying, and breaking up to obtain the modified basalt fiber.
5. The marine engineering anticorrosion coating according to claim 4, characterized in that: The diameter of the basalt fiber is less than 15 μm, and the length of the basalt fiber is 0.5 mm to 1.5 mm; the mixing is ultrasonic mixing, the frequency of the ultrasonic mixing is 30 kHz to 40 kHz, and the time of the ultrasonic mixing is 10 min to 30 min.
6. The marine engineering anticorrosion coating according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: mixing and preparing a modified liquid III according to a mass ratio of ethanol: pentaerythritol stearate: cellulose nitrate: sodium hexametaphosphate = 100: (1-3): (1-3): (0.5-1); adding carbon nanotubes to the modified liquid III according to a mass ratio of modified liquid III: carbon nanotubes = 150: (10-15), mixing, distilling and recovering ethanol, and drying and breaking up to obtain the modified carbon nanotubes.
7. The marine engineering anticorrosion coating according to claim 6, characterized in that: The particle size range of the carbon nanotubes is below 100 nm; the mixing is ultrasonic mixing, the frequency of the ultrasonic mixing is 30 kHz to 40 kHz, and the time of the ultrasonic mixing is 20 min to 50 min.
8. The marine engineering anticorrosion coating according to claim 1, characterized in that: The preparation method of the plant extract comprises the following steps: mixing and crushing the Kandelia kandelii leaves and the Magnolia officinalis leaves in a mass ratio of (5-10):(1-3) to obtain a mixture, performing percolation extraction with ethanol of 6 to 8 times the mass of the mixture to obtain an leaching solution, distilling and recovering the ethanol, and drying and breaking up the mixture to obtain the plant extract.
9. The marine engineering anticorrosion coating according to claim 1, characterized in that: The particle size range of the nano silicon dioxide is below 100nm; the particle size range of the nano zinc oxide is below 100nm; the particle size range of the nano titanium dioxide is below 100nm; the diameter range of the carbon fiber is below 10μm, and the length is 0.5mm to 1.5mm; the particle size range of the zinc phosphate is below 5μm.
10. A method for preparing an anti-corrosion coating for marine engineering, used for preparing an anti-corrosion coating for marine engineering according to claim 1, characterized in that: The preparation method comprises the following steps: S1: Mix nano silicon dioxide, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions, then add carbon fiber and zinc phosphate, and mix them by air flow to obtain a mixture A; S2: According to the mass proportions, butyl acetate and mixture A are mixed evenly at a high speed of 1000 r / min to 1500 r / min, and then fluorocarbon resin, terminal hydroxy polybutadiene, fluorine-modified acrylate leveling agent and silicone defoaming agent are added and mixed evenly, and then plant extracts and organotin are added and mixed evenly, and finally modified synthetic mica, modified basalt fiber and modified carbon nanotubes are added, and mixed at a low speed of 300 r / min to 500 r / min for 30 min to 50 min to obtain a coating.
Citation Information
Patent Citations
Microstructured multifunctional inorganic coating additives for preventing fouling (growth of biofilm) in aquatic applications
CN101993623A
Weather-resistant shock-resistant anticorrosive coating
CN105176347A
Carbon nanotube dispersion, method for producing same, and conductive molded body
CN108883937A
Marine anticorrosive paint capable of preventing microbial adsorption
CN112662299A
On-line dyeing water-resistant colored basalt fiber and preparation method thereof
CN115010373A
Cited By
High-solid nano fluorocarbon primer
CN120098491A
High solid nano fluorocarbon primer
CN120098491B